ANALYSIS OF SUPPLIER SELECTION FOR PROCUREMENT OF GOODS IN KITCHEN AT LOR IN NEW KUTA HOTEL - Doni Eko Prasetyawan; I Gusti Putu Sutarma; I Ketut Astawa (Politeknik Negeri Bali, 2018)
The process of procurement of goods and food materials obtained through the process or purchase activities. Purchasing or purchasing is a process of searching the source and ordering of goods or services to assist the production function in the production or service activities (Fausi, 1995: 1004). This research is titled